2017
DOI: 10.18203/2394-6040.ijcmph20175086
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and pathological trends in oral squamous cell carcinoma in a local tertiary care hospital

Abstract: Background: Cancer archives perform a dynamic role in observing the prevalence of these cancers. The present study was carried out to study the epidemiological and pathological trends of oral squamous cell carcinoma (OSCC) in a local tertiary care hospital. Methods: Tissue samples were taken from the adult patients of both genders undergoing surgery for OSCC after an informed consent following the inclusion and exclusion criteria. Socio-demographic information was obtained along with relevant clinical, laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
4
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
(13 reference statements)
5
4
1
1
Order By: Relevance
“…The most common histopathologically variant of OSCC reported by our study was WDSCC (40%) followed by MDSCC (28%) and PDSCC (12%). Our study showed results (Table 4) which are in accordance with other studies reported, such as WDSCC (35%) by Siriwardena et al and Gul et al (42.5%) of WDSCC 18,22 . These findings were different from some previous studies reported by Remin et al who showed increased cases among moderately (42%) and poorly differentiated squamous cell carcinomas (15%) 24 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The most common histopathologically variant of OSCC reported by our study was WDSCC (40%) followed by MDSCC (28%) and PDSCC (12%). Our study showed results (Table 4) which are in accordance with other studies reported, such as WDSCC (35%) by Siriwardena et al and Gul et al (42.5%) of WDSCC 18,22 . These findings were different from some previous studies reported by Remin et al who showed increased cases among moderately (42%) and poorly differentiated squamous cell carcinomas (15%) 24 .…”
Section: Discussionsupporting
confidence: 93%
“…The present study observed a mean age of 56.52 for OSCC cases and a male-female ratio of 1.6:1 was observed. This finding is supported by studies reported by Mirza et al, and Gul et al, who observed a male-female ratio of 1.6:1 6,18 . While this finding is contrary to Beena et al, who observed that most cases were reported in the younger age group (77%) 19 .…”
Section: Discussionsupporting
confidence: 87%
“…Al analizar el grado de diferenciación histopatológico encontramos resultados similares a los obtenidos en nuestro estudio, Wei-ping Jie y col. reportan el 90,8% de los casos fueron los COCE bien diferenciados y moderadamen-te diferenciados (38) . Otros estudios mostraron datos similares, Sairay col. en Pakistán para el período 2015-2016 mostró que el 52% de los COCE fueron moderadamente diferenciados y el 42% bien diferenciados (39) , mientras Gul y col. obtuvieron en un Hospital terciario del sur de Punjab India, un 43% de pacientes con COCE bien diferenciado, 38% moderadamente diferenciado y 20% con COCE indiferenciado (40) . Leite y col. en 2018 en un estudio de Brasil de COCE en una población de bajo desarrollo económico, n=194 casos, el 54,6% fueron bien diferenciados, 37,1% moderadamente diferenciados y 5,2% carcinomas indiferenciados, este estudio reporta un perfil similar a nuestro estudio (41) .…”
Section: Discussionunclassified
“…[5] Currently, with therapeutic breakthroughs, cancer now fits into a new category of manageable chronic diseases, which is largely achieved through modification in lifestyle, timely diagnosis and proper management. [6] But regardless of being in anatomic sites easily accessible for clinical examination and inspite of recent diagnostic and therapeutic advances, OSCC's still remains to be a condition with poor prognosis, as the disease is often diagnosed at an advanced stage. Most frequent reasons are the early wrong diagnosis and the ignorance from the patient and/or attending physician or dentist.…”
Section: Introductionmentioning
confidence: 99%